(untitled) (Research, Society and Development, 2021)
Objective: to analyze the possible changes and impacts that the COVID-19 pandemic brought to the standard of production of the Oral Health Teams (ESB) of the Primary Health Care of Pernambuco. Methodology: this is a descriptive study with a quantitative approach, with comparative analysis of records of dental procedures from the year prior to the COVID-19 pandemic (March 2019 to March 2020) and the first year of the pandemic (March 2020 to March 2021), using data from the SUS Outpatient Information System. Results: the number of dental procedures in the first year of the pandemic was 75% lower compared to the previous year. In this pandemic period, tooth extractions were more frequent than restorative procedures, which reveals how much the historical culture of the population still prevails in seeking care only in the more advanced stages of oral diseases, in addition to the fact that, in different periods of the year, dental care was restricted to urgencies and emergencies. Conclusions: An underutilization of the workforce and expertise of the ESB professionals was observed, which could have been better utilized in "out-of-office" services during the pandemic. The appreciation of dental professionals and the Brasil Sorridente program as a all, so that free and quality dentistry reaches more and more Brazilians.